2017
DOI: 10.1371/journal.pone.0182030
|View full text |Cite
|
Sign up to set email alerts
|

C77G in PTPRC (CD45) is no risk allele for ovarian cancer, but associated with less aggressive disease

Abstract: The pan lymphocyte marker CD45 exists in various isoforms arising from alternative splicing of the exons 4, 5 and 6. While naïve T cells express CD45RA translated from an mRNA containing exon 4, exons 4–6 are spliced out to encode the shorter CD45R0 in antigen-experienced effector/memory T cells. The SNP C77G (rs17612648) is located in exon 4 and blocks the exon’s differential splicing from the pre-mRNA, enforcing expression of CD45RA. Several studies have linked C77G to autoimmune diseases but lack of validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Quan et al identified BRWD1 and its corresponding biological processes involved in the development of AD by constructing an AD protein interaction network [31]. PTPRC was identified as Parkinson's disease biomarker [32] and in lung adenocarcinoma, latent tuberculosis, and ovarian cancer, PTPRC served as a key hub gene and was highly associated with disease [33][34][35]. These results suggest that the constructed LASSO model could provide valuable clues for researchers Computational and Mathematical Methods in Medicine to identify key AD-related diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al identified BRWD1 and its corresponding biological processes involved in the development of AD by constructing an AD protein interaction network [31]. PTPRC was identified as Parkinson's disease biomarker [32] and in lung adenocarcinoma, latent tuberculosis, and ovarian cancer, PTPRC served as a key hub gene and was highly associated with disease [33][34][35]. These results suggest that the constructed LASSO model could provide valuable clues for researchers Computational and Mathematical Methods in Medicine to identify key AD-related diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ZAP70, PTPRC, FYN and WASP2 were found to be dysregulated in different cancers including breast, leukemia, colorectal cancer, etc. [40][41][42][43]. However, none of the studies showed any linkage of these seven genes with delayed tumor recurrence in HCC.…”
Section: Discussionmentioning
confidence: 98%
“…PTPRC is expressed on all nucleated cells of the hematopoietic system. It expresses several isoforms specific to a certain cell type and cell development or activation state [ 19 ]. PTPRC also plays an important role in autoimmune diseases and cancers, as well as in infectious diseases; its deficiency may lead to T and B lymphocyte dysfunction, manifesting as severe combined immunodeficiency [ 20 ].…”
Section: Discussionmentioning
confidence: 99%